The nature of early memory an adaptive theory of the genesis and development of memory - Howe, Mark L. (New York ; Oxford : Oxford University Press, 2011)
Howe presents an exegesis of the research and theory concerning the emergence and development of long-term memory from birth through adolescence. The book also contains a presentation of Howe's theory that memory is an adaptive mechanism that guides the development and survival of the organism in a changing environment.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Long-term memory in children; Long-term memory in adolescence; Memory